The USA and India: mutual perceptions and political actions - Rothermund, Dietmar (The impact of Asian powers on global developments, 2004)
Political actions in the field of international relations are influenced by a multitude of perceptions of the other. Basically, one can distinguish between two levels of perception. Current events, for instance, claim immediate attention. Reports about successful or disappointing state visits, or television news of disaster etc. have a direct impact on such perceptions. But there are also other, longer-term, images embedded in our memories. The American author, Harold Isaacs, called them “Scratches on Our Minds” when he published his report on U.S. perceptions of China and India in 1957. Such “scratches” shape our frame of reference when we think about current issues and each generation has its own “scratches”. Some of them are so to speak inherited; others are influenced by more recent ideas. The view of India held by many older Americans, for example, was shaped by missionary reports. In the eyes of the missionaries, the Hindu was the archetype of the benighted heathen who resisted all attempts to convert him. The missionaries had more sympathy with the Muslims and showed great admiration for the polite and pragmatic Chinese.